EVALUASI PINJAMAN PENGUATAN MODAL BIDANG TANAMAN PANGAN DAN HORTIKULTURA DI KECAMATAN PAKEM KABUPATEN SLEMAN - Hani Perwitasari; Ken Suratiyah; Suhatmini Hardyastuti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2011)
The objectives of this research -were (1) to identify the farmer groups's members reasons in taking the capital reinforcement loan, (2) to identify the capital reinforcement loan realization accepted by the members offarmer groups, (3) to identify the using of capital reinforcement loan by the members of farmer groups, (4) to identify the benefit of capital reinforcement loan according to the perception offarmer groups members. Basic method used in this research was descriptive method Research population was the member offarmer groups who took capital reinforcement loan of food and horticulture in Pakem district of Sleman regency in 2007, while research respondent was 39 members of 13 farmer groups' took by random sampling. The result of this research sho-wedthat thefarmer groups' reasons in taking the capital reinforcement loan the same with the amount of the loan demanded by the members of farmer groups. The capital reinforcement loanfor thefarmer groups' members has been usedfor onfarm. According to the perception of farmer groups members, the capital reinforcement loan was very useful because it could increase the income, production, and